The Effect Of Adding Iron Powder Waste On Soil Carrying Capacity Case Study Of Soil In Kedungpring District - Feby Taufiqu Rahmah; Nur Indah Mukhoyyaroh (Jurnal Scientia, 2024)
Land is useful as a support for building foundations and as a building material itself. Factors that affect the bearing capacity of the soil include: soil type, density level, water content, and others. Human activities in meeting their needs sometimes cause soil mobilization. For that, it is necessary to improve the shrinkage properties of the soil. The purpose of this study is to analyze the California Bearing Ratio (CBR) value of clay soil with the addition of iron powder waste as a mixture, which is expected to be able to strengthen the bearing capacity of the soil in the soil pavement layer. The purpose of this study was to determine how much influence the addition of iron powder waste to clay soil has on the California Bearing Ratio (CBR) value. The methods used are direct shear test and CBR test. By going through the stages of testing including, water content testing, soil specific gravity testing, wet volume testing, dry volume testing, plastic limit testing, liquid limit testing, free pressure testing, standard density testing, California Bearing Ratio (CBR) test, and direct shear test. It is known from the results of the CBR Test, the CBR value of the soil increased from normal soil testing by 2.65% to 3.48% after adding a mixture variation of 5% iron powder, to 3.10% after adding a mixture variation of 10% iron powder, and there was a decrease after adding a mixture variation of 15% iron powder by 2.66% and for direct shear testing (Direct Shear Test) there was an increase of 12.7217 kg/cm2 in the 10% iron powder mixture variation.